1999 Financial report: BRAC RDP/RCP programme - Kelley, Brian; Pikholz, Lynn (Shorebank Advisory Services, 2016)
1. Portfolio risk management and credit related activities 2. Management and analysis of savings activities 3. Branch and BRAC financial sustainability 4. Development of BRAC RLF reporting 5. Other areas of special donor concern 6. Risk management, capital adequacy 7. Beyond 2000 8. Recommendations for technical support 9. Summery of major recommendations